Performance of Bluetooth in Homogeneous Environment - S. Shirsat, A.; A. Shirsat, S.; M. Yadav, D. (International Journal of Engineering and Technology, 2018)
Various wireless technologies use unlicensed ISM band in a frequency range 2.4GHz. Due to collocated, services causes mutual interference to one other; it degrades performance regarding Bit Error Rate (BER) and consequently throughput. The Bluetooth occupies less bandwidth and low power, gets more hampered as compare to other high bandwidth services is referred to as the heterogeneous environment. In this paper, an attempt is made to calculate the performance of basic rate Bluetooth in the presence of other Bluetooth devices in the close vicinity. The MATLAB based simulation results showed the degradation of performance of Bluetooth and enriched by selecting different hopping frequency in synchronisation with interfering Bluetooth devices.Â Â